Contribuição do humanismo integral para a teologia: Doutrina Social da Igreja - Calandrin, Gustavo Braz (2025)
Integral Humanism aims to highlight the totality that makes up the human being in life. It is not merely a fleeting search for achievements, but rather instruments that fulfill human existence in all its aspects, ensuring that nothing is lacking, encompassing the material and immaterial dimensions, body and spirit, from which the human being is understood. Many people around the world and in various societies experience the dismantling of integral thinking, as they are faced with scarcity, the lack of opportunity to develop and, in extreme cases, the right to survive, depending on their own luck to maintain their existence. Jacques Maritain is one of the great architects of the explanation of integral humanism, the source from which the Social Doctrine of the Church drew, and for this reason he developed a fabulous Compendium, which, through the Justice and Peace Commission, uses Christian thought as a powerful weapon against the attacks of the contemporary period that has a more individualistic view. Based on this effort, Christians, supported by the humanist cause, work hard to safeguard and dignify human life